Small-world and Scale-free Features in Harry Potter - Zhang Jun; Zhao Hai; Xu Jiu-qiang; Wang Jin-fa (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Harry Potter is a series of seven fantasy novels which has got a huge success. To explore the reasons of so successful of the novel behind, we analyzed the characters network in Harry Potter from the perspective of complex networks. Studies show that the characters network in Harry Potter has got the small-world effect and scale-free feature. It is a typical complex network. The success of novel Harry Potter is precisely due to the complex properties of it, and this may give some guidance for novel writers when preparing their works.